INFLUENCE OF MgO ON MICROSTRUCTURAL AND MECHANICAL PROPERTIES OF RAW CLAY FROM BURKINA FASO - MOHAMED SEYNOU; YOUNOUSSA MILLOGO; LAMINE ZERBO; RAGUILNABA OUEDRAOGO (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The influence of MgO on mechanical and microstructural properties of raw clay material from Burkina Faso was investigated by means of X-ray diffraction, scanning electron microscopy, infrared spectroscopy, differential thermal analysis and numerical simulation. The mineralogical composition was modified with the formation of new crystalline phases such as mullite, spinel – Mg, enstatite and forsterite. During the sintering and with add of MgO, the mullite quantity decrease contrary to forsterite and affect the different properties of sintered products. The mechanical properties were improved with MgO amount around 2 – 5 wt%. For magnesia amount higher than 5 wt%, the magnesia is not entirely consumed and is originated to the formation of pores in the manufactured products which are detrimental to the mechanical properties.